Molecular mechanisms of rapid-acting antidepressants: New perspectives for developing antidepressants - Tao Chen; Ling Cheng; Jingwen Ma; Jiyuan Yuan; Chao Pi; Linjin Xiong; Jinglin Chen; Huiyang Liu; Jia Tang; Yueting Zhong; Xiaomei Zhang; Zerong Liu; et al. (Elsevier, 2023)
Major depressive disorder (MDD) is a chronic relapsing psychiatric disorder. Conventional antidepressants usually require several weeks of continuous administration to exert clinically significant therapeutic effects, while about two-thirds of the patients are prone to relapse of symptoms or are completely ineffective in antidepressant treatment. The recent success of the N-methyl-D-aspartic acid (NMDA) receptor antagonist ketamine as a rapid-acting antidepressant has propelled extensive research on the action mechanism of antidepressants, especially in relation to its role in synaptic targets. Studies have revealed that the mechanism of antidepressant action of ketamine is not limited to antagonism of postsynaptic NMDA receptors or GABA interneurons. Ketamine produces powerful and rapid antidepressant effects by affecting α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptors, adenosine A1 receptors, and the L-type calcium channels, among others in the synapse. More interestingly, the 5-HT2A receptor agonist psilocybin has demonstrated potential for rapid antidepressant effects in depressed mouse models and clinical studies. This article focuses on a review of new pharmacological target studies of emerging rapid-acting antidepressant drugs such as ketamine and hallucinogens (e.g., psilocybin) and briefly discusses the possible strategies for new targets of antidepressants, with a view to shed light on the direction of future antidepressant research.